Losses on maize harvesting according to the water content of the grains at harvest - Galindo, Fernando Shintate [UNESP]; Zocoler, Joao Luis [UNESP]; Minhoto Teixeira Filho, Marcelo Carvalho [UNESP]; Buzetti, Salatier [UNESP]; Alves, Cleiton Jose [UNESP]; Kondo Santini, Jose Mateus [UNESP] (Univ Estadual Mato Grosso Sul, 2019)
The use of methodologies for easy application and quick results are important in determining the water content in the grains to maize producers could decide the right time to perform the harvest with reduced losses in maize grain yield with natural drying at field conditions. The objective of this work was to study the ideal water content at grains at harvest of maize crop, yield and production components as well as losses from natural drying in the field at different water contents at grains harvest. The experimental design was of randomized blocks with 4 repetitions and the treatments consisted in the harvest of the following average levels of water contents of grains on a wet basis: 28.9 (point of full physiological maturity), 23.5, 21.9, 18.9, 16.1 and 13.8%. All variables evaluated were influenced by moisture in grain harvest, having presented increasing linear regression for the number of ears per hectare, final population of plants per hectare and grain potential productivity. The quadratic regression was the best for grain productivity, with the maximum point of productivity of 10,220 kg ha(-1) achieved at 23.3% of water content in grain harvest.
Keywords: Zea mays; grain humidity for harvest; grains productivity; components production